2017
DOI: 10.1007/s10147-017-1159-1
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis survey of appropriate bone turnover markers in the detection of bone metastasis in lung cancer

Abstract: The present meta-analysis suggested that serum measurement of TALP, BALP, ICTP and NTX might be helpful in detecting BM in lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Why moderate increases in circulating ALP are also associated with higher lung cancer incidence is unclear. One possibility might be that high ALP levels appear to be independent predictors for bone metastases that are commonly detected in patients with lung cancer 33 34. Thus, high ALP levels might be associated with lung cancer risk due to these unrecognised bone metastases years prior to a cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Why moderate increases in circulating ALP are also associated with higher lung cancer incidence is unclear. One possibility might be that high ALP levels appear to be independent predictors for bone metastases that are commonly detected in patients with lung cancer 33 34. Thus, high ALP levels might be associated with lung cancer risk due to these unrecognised bone metastases years prior to a cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Serum concentrations of TRACP were found increased in patients with bone metastases from breast cancer, but not lung cancer (90,155). In prostate cancer, high NTX and CTX levels were associated with bone metastases (35).…”
Section: Diagnosis Of Bone Metastasismentioning
confidence: 92%
“…Furthermore, a meta-analysis including 19 trials and 3,628 patients with solid tumors showed that serum BALP levels in patients with bone metastases were 2.9-fold higher (P < 0.05) than in patients without bone lesions (91). Another meta-analysis in lung cancer including 16 trials and 1,720 patients with or without bone metastases showed that high concentrations of BALP were also associated with bone metastasis (155).…”
Section: Diagnosis Of Bone Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…32 Recent study of meta-analysis showed the clinical significance of bone turnover markers such as total alkaline phosphatase, BAP, ICTP and NTX for the diagnosis of bone metastasis in lung cancer, but TRACP-5b was not correlated. 33 In our study, high early post treatment ICTP was associated with progression of bone disease, SREs and increasing risk of death after treatment with the bone modifying agents for lung cancer bone metastasis. Although the situation is different, both have shown the usefulness of ICTP in lung cancer bone metastasis.…”
Section: Discussionmentioning
confidence: 50%